Maternal occupation during pregnancy, birth weight, and length of gestation: combined analysis of 13 European birth cohorts - Casas, Maribel; Cordier, Sylvaine; Martínez, David; Barros, Henrique; Bonde, Jens Peter; Burdorf, Alex; Costet, Nathalie; dos Santos, Ana Cristina; Danileviciute, Asta; Eggesbø, Merete; Fernandez, Mariana F.; Fevotte, Joelle; et al. (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVES ': 'We assessed whether maternal employment during pregnancy – overall and in selected occupational sectors – is associated with birth weight, small for gestational age (SGA), term low birth weight (LBW), length of gestation, and preterm delivery in a population-based birth cohort design. ' ' METHODS ': 'We used data from >200 000 mother-child pairs enrolled in 13 European birth cohorts and compared employed versus non-employed women. Among employees, we defined groups of occupations representing the main sectors of employment for women where potential reproductive hazards are considered to be present. The comparison group comprised all other employed women not included in the occupational sector being assessed. We performed meta-analyses of cohort-specific estimates and explored heterogeneity. ' ' RESULTS ': 'Employees had a lower risk of preterm delivery than non-employees [adjusted odds ratio (ORadj) 0.86, 95% confidence interval (95% CI) 0.81–0.91]. Working in most of the occupational sectors studied was not associated with adverse birth outcomes. Being employed as a nurse was associated with lower risk SGA infants (ORadj 0.91, 95% CI 0.84–0.99) whereas food industry workers had an increased risk of preterm delivery (ORadj 1.50, 95% CI 1.12–2.02). There was little evidence for heterogeneity between cohorts. ' ' CONCLUSIONS ': 'This study suggests that, overall, employment during pregnancy is associated with a reduction in the risk of preterm birth and that work in certain occupations may affect pregnancy outcomes. This exploratory study provides an important platform on which to base further prospective studies focused on the potential consequences of maternal occupational exposures during pregnancy on child development.
Keywords: birth cohort; birth weight; cohort study; Europe; European birth cohort; length of gestation; low birth weight; maternal occupation; meta-analysis; pregnancy; preterm delivery; small for gestational age